Hierarchies of Evidence Applied to Lifestyle Medicine (HEALM): Introduction of a Strength-of-evidence Approach Based on a Methodological Systematic Review (P13-023-19). (13th June 2019) - Katz, David; Karlsen, Micaela; Chung, Mei; Shams-White, Marissa; Green, Lawrence; Fielding, Jonathan; Saito, Ayumi; Willett, Walter
Abstract: Objectives: To characterize strength of evidence (SOE) tools in recent use, identify their application to lifestyle medicine, and to assess implications of the findings. Methods: The search strategy was created in PubMed and modified as needed for four additional databases: Embase, AnthropologyPlus, PsycINFO, and Ageline. Systematic reviews and meta-analyses were included if they used a specified SOE tool. There were seven interventions or exposures of interest: diet, exercise, stress, social relationships/support, addiction(s), sleep, and genetic-based factors with potential for epigenetic modification. Data was collected for each SOE tool and summarized in narrative form with regard to the conditions necessary for assigning the highest SOE grading and treatment of prospective cohort studies within each SOE rating framework was qualitatively summarized. The expert panel convened to discuss the findings and their implication for assessing evidence in the domain of lifestyle medicine. Results: A total of 15 unique tools were identified. All tools rated SOE using three to five levels of evidence, with the exception of one that uses two levels. Ten were tools developed and used by governmental agencies or other equivalent professional bodies and were applicable in a variety of settings. Five require consistent results from RCTs of high quality to award the highest rating of evidence. Except for the Oxford Centre for Evidence-Based Medicine (OCEBM) Levels of Evidence, specific mention of cohort studies was made only to note their secondary contribution to overall SOE as compared to RCTs, unless RCTs were methodologically flawed. A new construct, Hierarchies of Evidence Applied to Lifestyle Medicine (HEALM), was developed to evaluate SOE for the lifetime effects of health behaviors. Conclusions: The best metric for SOE varies with research questions and the methods required to answer them. Assessment of evidence relevant to lifestyle medicine requires a potential adaptation of SOE approaches when outcomes and/or exposures obviate exclusive or preferential reliance on RCTs. Funding Sources: Supported by the American College of Lifestyle Medicine, with additional funding from the Centers for Disease Control, grant 5U48DP005023–04. Supporting Tables, Images and/or Graphs: